The association between two categorical variables measured by chi-square statistic, w index and contingency coefficient - Erika Liptaková (Matej Bel University, 2022)
This paper provides a brief overview of analysis of dependence between two categorical variables. It shows the calculation of the chi-square test, as well as its effect size using w index and the calculation of the measures of associations. DOI: https://doi.org/10.24040/sjss.2021.7.2.50-55